80: Treatment of Pulmonary Arterial Hypertension Using Sildenafil in Neonates with Bronchopulmonary Dysplasia. Issue 6 (1st June 2014) - Trottier-Boucher, M; Lapointe, A; Malo, J; Fournier, A; Raboisson, M; Martin, B; Moussa, A
Abstract: BACKGROUND: Sildenafil citrate, a phosphodiesterase-5-inhibitor, is a controversial treatment option for pulmonary arterial hypertension (PHT), a significant complication of bronchopulmonary dysplasia (BPD).There is scarce data in premature infants. OBJECTIVES: Evaluate the use of sildenafil citrate in infants with BPD complicated by PHT. DESIGN/METHODS: Retrospective cohort study in a level 3 NICU. All medical records of premature infants with PHT secondary to BPD treated with sildenafil citrate between January 2009 and May 2013 were reviewed. Primary outcomes were: Clinical response with 20% decrease in: respiratory support score or FiO2 requirements Echocardiographic response with decrease in tricuspid regurgitation gradient (at least 20%) or septal flattening (at least one degree) RESULTS: Twenty three infants (61% male) with a median (IQR) gestational age of 26 weeks (23 to 30weeks) and birth weight of 710 g (480 g to 1170 g) were included. Antenatal data is marked by presence of chorioamnionitis (17%), oligohydramnios (22%), intrauterine growth retardation (39%) and premature rupture of membranes (39%). Neonatal course included: confirmed sepsis (48%), grade 2 or more necrotizing enterocolitis (32%), stage 3 retinopathy of prematurity (ROP) (56%) and patent ductus arteriosus (78%). Pharmacologic data, benefits and side effects are represented in the table. CONCLUSIONS: Sildenafil citrate treatment for patients with PHT